Respuesta :

Work backwards.

Start with z = 4.

Now deal with the middle equation

y + 3z = 11                    Substitute z = 4 and solve for y

y + 3(4) = 11                  Subtract 12 from both sides

y + 12 = 11

y + 12 - 12 = 11 -12         Combine terms on the left and right

y = - 1                             Now use the top equation for x

z = 4                              z still = 4

2x + 4(-1) +3(4) = 14

2x - 4 + 12 = 14              Solve 3z

2x + 8 = 14                     Subtract 8

2x + 8 - 8 = 14 - 8          Combine

2x = 6                            Divide by 2

x = 6/2

x = 3

Answer

x = 3

y = - 1

z = 4